How to Check a forest Fire - Ani, J. R. (Indian Forester, 2000)
Forest fires cause unfathomable losses to the whole forest ecosystem. Mild fires can augment the germination of seeds like that of Melia composita and Tectona grandis and can help maintain the moist deciduous status of a forest having valuable timber species from progressing to moisture types. Uncontrolled fires cause surface compaction, enhanced run-off and subsequent floods. It also kills the soil microbes and change the chemical properties of the soil. The existing preventive measures in India are very poor compared to those in vogue in Western countries. A fire plan for each vulnerable area is an imperative to check and fight fires. Mopping up operations and tracing down the culprits are also inevitable measures to ward off any decimating fire in the future.